Fuzzy extensions of PROMETHEE: Models of different complexity with different ranking methods and their comparison - Yatsalo, Boris; Korobov, Alexander; Öztaysi, Basar; Kahraman, Cengiz; Martínez, Luis (Elsevier BV, 2021)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: fuzzy numbers; Decision theory; ranking of fuzzy numbers; standard fuzzy arithmetic; overestimation problem; Mathematical economics and fuzziness; fuzzy PROMETHEE; violation of the basic FMCDA axiom; fuzzy MCDA; Theory of fuzzy sets, etc.; transformation methods